CONDITION, PROBLEMS AND TRENDS OF MEDICO-SOCIOLOGICAL RESEARCHES OF PUBLIC HEALTH AND HEALTH SYSTEM - Кожевников, Андрей Александрович (Medicine in Kuzbass, 2017)
In article by the analysis of domestic and foreign publications, other information sources the most popular are considered and the methodological approaches having practical application connected with assessment of public health and a health care system. A predictive conclusion about what unlike other types of ensuring medical activity of medico-sociological providing allows to expand idea of activity of subjects of a health care system due to establishment of target interrelation of socially oriented integrated indicators is formulated, to estimate health and quality of life of the population. Objective. Methodological approaches to assessment of public health and health care system. Methods. Comparative analysis. Results. Application of the system focused complex of the interconnected medico-sociological methods of a research allows to organize interdepartmental interaction at the qualitative level and to achieve goals. Conclusions. The considered methodological approaches have introduced on the one hand understanding of need of creation the most adapted, adequate to real requirements and opportunities of population of systems and forms of the organization not only health care, medical care, but also the most social environment. On the other hand these theories have helped to generalize regularities of emergence and development of pathological states and processes for the purpose of formation and maintaining health.